Comparison of the effect of emotional intelligence training and yoga exercises on social anxiety of women with depression - Maryam Mirzaei (Novelty in Clinical Medicine, 2023)
Background: Depression is the most common mood and emotional disorder and the biggest mental illness of this century. One of the common problems of participant with depression is social anxiety.Objectives: The aim of this study was to compare the effect of emotional intelligence training and yoga exercises on social anxiety in women with depression.Methods: The present research method was Quasi-experimental. In order to select the research sample, after entering the counseling and psychotherapy centers of Tabriz city, 60 participants with depression disorder who had a case in that center, were selected as available and Then, among these participant, 45 participants were randomly replaced in two experimental groups and a control group. For the first group of emotional intelligence training (10 sessions; one session of 90 minutes per week) and for the second group, qigong exercises (8 weeks; two sessions per week, 75 minutes) were applied and the control group did not receive training. All participant in the sample group filled in Leibovitz's social anxiety questionnaire (1987) in the pre-test and post-test stages and Beck's depression questionnaire in the pre-test stage. One-variable covariance analysis was used to analyze the data.Results: The results showed that the average scores of social anxieties in depressed women in the emotional intelligence training group (32/61) compared to the yoga exercises group (34/38) and in yoga exercises group compared to the control group (38/88) in the post-test decreased significantly (p<0.05).Conclusion: The findings showed that emotional intelligence training is more effective than yoga exercises in reducing social anxiety in women with depression.